Biological activities supporting development of cosmeceutical skin products from Wedelia trilobata (L.) Hitch. flower extract - Junlatat, Jintana; Peng-ngummuang, Kanyarat; Thorajake, Piyaporn; Fangkrathok, Niramai; Sripanidkulchai, Bungorn (Agriculture and Natural Resources, 2023)
Importance of the work: This is the first report to demonstrate the potential of Wedelia trilobata (L.) Hitch. as an ingredient in cosmeceutical products. Objectives: To examine the biological activities associated with cosmeceutical products of W. trilobata extract. Materials & Methods: The flowers (WTF), leaves (WTL) and stems (WTS) of W. trilobata were separately extracted using 50% ethanol and freeze-drying to obtain WTF, WTL and WTS extracts, respectively. Then, the antioxidant, anti-tyrosinase, antimicrobial, cytoprotective and anti-inflammatory activities of the extracts were investigated. Results: Screening tests, using the three extracts of the plant showed different positive effects, with WTF having the highest antioxidant, tyrosinase and nitric oxide inhibitory activities. Therefore, WTF was further studied to find the mechanisms involved in anti-inflammatory, antimicrobial and cytoprotective effects. WTF at concentrations of 50–200 μg/mL down-regulated the expression of cyclooxygenase-2 (COX-2), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) genes in macrophages using a semi-quantitative reverse-transcriptase polymerase chain reaction technique and the production of tumor necrosis factor-α in keratinocytes. The antimicrobial activity of WTF was demonstrated on many bacteria and Candida albicans. WTF prevented H2O2-induced cell death of human keratinocyte via down-regulation on the expression of matrix metalloproteinase-1(MMP-1) and MMP-2 genes and up-regulation on the expression of procollagen type 1 genes. The gel formulations containing WTF were developed with good stability and inhibited the growth of Propionibacterium acnes at statistically significant levels. Main finding: W. trilobata flowers demonstrated a potential source of an active ingredient in skin product development. The plant may have more value-added components for application in cosmeceuticals as well as being useful as a ground cover weed.